A Semiempirical Approach to the Determination of Daily Erythemal Doses. (16th April 2018) - Silva, Abel A.; Yamamoto, Ana L. C.; Corrêa, Marcelo P.
Abstract: The maintenance of ground‐based instruments to measure the incidence of ultraviolet radiation (UVR) from the Sun demands strict and well‐developed procedures. A piece of equipment can be out of service for a couple of weeks or months for calibration, repair or even the improvement of the facilities where it has been set up. However, the replacement of an instrument in such circumstances can be logistically and financially prohibitive. On the other hand, the lack of data can jeopardize a long‐term experiment. In this study, we introduce a semiempirical approach to the determination of the theoretical daily erythemal dose (DEDt ) for periods of instrumental absence in a tropical site. The approach is based on 5 years of ground‐based measurements of daily erythemal dose (DED) linearly correlated with parameters of total ozone column (TOC) and reflectivity ( R PC ) from the Ozone Monitoring Instrument (OMI) and the cosine of solar zenith angle at noon (SZAn ). Seventeen months of missing ground‐based data were replaced with DEDt, leading to a complete 5‐year series of data. The lowest and the highest values of typical DED were 2411 ± 322 J m −2 (1 σ ) (winter) and 5263 ± 997 J m −2 (summer). The monthly integrated erythemal dose (mED) varied from 59 kJ m −2 (winter) to 162 kJ m −2 (summer). Both of them depended mainly on cos(SZAn ) and R PC . The 12‐month integrated erythemal dose (12‐ED) ranged from 1350 kJ m −2 to 1546 kJ m −2, but it can depend significantly on other atmospheric parameter (maybe aerosols) not explicitly considered here. Abstract : Monthly integrated erythemal dose in Belo Horizonte (19.92°S, 43.94°W, 858 m a.s.l., 331 km², Brazil) for 5 years (2005–2010). Uncertainties are 1 σ . For a very good coefficient of determination of r 2 = 0.92, measured and calculated values follow both the seasonal influence of the solar zenith angle at noon and the monthly climatological influence of clouds. Doses range from 59 kJ m −2 (winter) to 177 kJ m −2 (summer), for a whole‐period average total ozone column of 255 ± 11 Dobson Units.